Development of Tourism Village in Gempol Village Karanganom District - Klaten Regency - Swantari, Anita; Wicaksono, Haryo (Jurnal Penelitian Pariwisata, 2020)
The purposes of this research are (1) to identify and evaluate internal and external factors, (2) to formulate strategy toward tourism village in Gempol village. Based on analysis result, Internal factor’s strength is the beauty and conservation of nature are the most significant influence on the development of tourism village. The most important weakness of Gempol village is not ready to receive the tourists, since the lack inadequate facilities.. External factor’s opportunity is the value of the people who always maintain and preserve traditional cultural. The most important threat is competition with others regions in the development of tourism village. The strategy taken is to maintain the harmony of nature and culture of the village. The need for a strong commitment from the entire village community. Promote village community training, including village government on tourism management, how to manage tourist attractions, guest or visitor management. Use all media to introduce and publicize tourism potential in the village both conventional and unconventional media, such as the internet media.